Retention system for implant-supported dentures used by brazilian dentists who work in implant dentistry - Saturnino Aparecido Ramalho; Fábio Pontes Dantas (Faculdade São Leopoldo Mandic, 2010)
Objective: To provide the dentists with support in the choice of the cement or screw type of retention for implant-supported dentures, according to the patient's problem. Methods: An opinion questionnaire was applied to a sample of 468 participants, all dentists working in the field of Implant Dentistry, of whom 272 (58.1%) participated in the 4th International Congress of Osseointegration of APCD, held in São Paulo (SP) from 6 to 9 May 2004, 119 (25.4%) participated in the 2nd International Congress of Implant Dentistry of Minas Gerais, between 10 and 12 June 2004 and 77 (16.5%) were professors and specialization and master students from São Leopoldo Mandic. Results: The results showed that 254 participants opted for the screw-retained system while 214 opted for the cement-retained system. Conclusion: There was a preference for the use of the screw-retained system, and that both cemented and screw-retained systems have advantages and disadvantages, so that the dentist is left to decide and evaluate them in order to indicate and use them with confidence in different clinical cases.